2021
DOI: 10.1007/s11187-021-00582-6
|View full text |Cite
|
Sign up to set email alerts
|

SME participation in research grant consortia—the emergence of coordinated attention in collaborative innovation

Abstract: influences priority setting. In this paper, we study attention coordination among SMEs and their partners for the emergence of priorities in joint research grant proposals. Applying content analysis to 207 grant proposals of innovation consortia that have received funding in the EU's Horizon 2020 program, we find that increasingly diverse consortia shift attention away from technological novelty and market creation towards more consideration for the innovation ecosystem.Plain English Summary SMEs in publicly f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 79 publications
(128 reference statements)
1
5
0
Order By: Relevance
“…A statement from one interviewed MNC showed that the R&I collaboration helped them to better communicate their 5G technology to potential clients and improved the design of the business model to supply these clients with the technology going forward. The findings with respect to SMEs is in line with the findings of Grimpe et al [19] regarding SMEs' focus on technological novelty, i.e., explicit innovation goals with their participation in R&I consortia.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…A statement from one interviewed MNC showed that the R&I collaboration helped them to better communicate their 5G technology to potential clients and improved the design of the business model to supply these clients with the technology going forward. The findings with respect to SMEs is in line with the findings of Grimpe et al [19] regarding SMEs' focus on technological novelty, i.e., explicit innovation goals with their participation in R&I consortia.…”
Section: Discussionsupporting
confidence: 89%
“…Reduced cost through shared spending on innovation and reference customer effects are also beneficial for SMEs [4]. MNCs' intentions to access funding is somewhat new, as the motivation behind R&I collaboration has usually been to monitor trajectories of different technologies and as a networking platform to widen their technological horizon [19]. The basis for this could be that the respondents represented R&I-related units from these MNCs, i.e., when the company budget allocated to R&I declines, searching for funding from other sources is necessary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1. Conducting joint R&D, including agreements on cooperation between universities and businesses to implement joint research activities, regardless of the funding source (Grimpe et al, 2021). 2.…”
Section: Current Collaboration Models From the Literaturementioning
confidence: 99%
“…Different entities may pursue different goals, preferring specific kinds of R&D outputs over others. Commercial products as R&D outputs are more valued by SMEs (Luukkonen, 2002) than HEIs (Grimpe et al, 2022). SMEs are more market-driven than research-driven (Hervás-Oliver et al, 2021).…”
Section: Research Questions and Literature Reviewmentioning
confidence: 99%